First experience with the new extracorporeal membrane oxygenation system Colibri - Saemann, Lars; Stiller, Markus; Willsch, Jan; Schultze, Thomas; Matin, Meradjoddin; Veres, Gábor; Szabó, Gábor (Artificial organs, 2024)
Introduction: Extracorporeal membrane oxygenation (ECMO) is increasingly used for circulatory or pulmonary support not only in-hospital but also out-of-hospital. Small dimensions and a lightweight design are important, especially for out-of-hospital use but also for intra-hospital transportation of patients who require ECMO support. We share our first experience with the new Colibri ECMO system. Patients and Methods: From December 2022 to January 2023, we used the new Colibri extracorporeal circulation (ECC) system in six patients with cardiac or pulmonary failure. Results: The Colibri system was used in-hospital in six patients with post-cardiac surgery low output syndrome, respiratory failure due to influenza or acute respiratory distress syndrome, cardiogenic shock, pulmonary embolism, and failed weaning from cardiopulmonary bypass. The system was implanted in venovenous (VV) and venoarterial (VA) fashion in 3 patients, respectively. In one patient, the configuration was switched from VA to VV after cardiac recovery. One patient received left-ventricular unloading using the IMPELLA((R))5.5. ECMO run time was 1 to 13 days. We did not notice any ECC system-associated complications. No ECMO system changes were required. Conclusion: Our case series concludes that the new Colibri system is safe and effective for in-hospital ECMO indications. The small dimensions and lightweight design are very beneficial for the transportation of patients. It might be especially helpful for out-of-hospital situations.